Improving Elementary School Students' Reading Literacy Through the Use of Picture Story Media - I Nengah Yusa Yusyana; Ni Nyoman Kurnia Wati; Ni Nyoman Lisna Handayani (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
Reading literacy serves as the primary foundation for elementary school students to master various disciplines. However, initial observations in Grade V of SD Negeri 9 Seraya indicated that students' reading literacy levels remained low, with only 40% of students achieving the minimum mastery criteria. This study aimed to examine the effectiveness of picture story media in improving students' reading literacy. The research employed a one-group pretest-posttest design (pre-experimental). The research subjects were 27 fifth-grade students. Data collection was conducted through reading literacy tests, observation sheets, and student response questionnaires. The instruments had been tested for content validity (I-CVI = 0.89) and reliability (Cronbach's Alpha = 0.82–0.85). Data were analyzed using descriptive statistics and paired sample t-tests. The results showed that reading mastery increased from 40% in the pretest to 78% in the posttest. The mean pretest score (58.4; SD=12.3) significantly increased to 78.6 (SD=10.1) in the posttest (t(26)=8.47; p<0.001; Cohen's d=1.63 [very large effect]). Student responses to the picture story media were in the very positive category (mean score 34.2 out of 40). This study concludes that picture story media has been proven effective and significant in improving elementary school students' reading literacy. This research recommends the consistent use of picture story media, particularly for students with low initial abilities.